THE IMPLEMENTATION OF BAITUL MAAL MANAGEMENT IN EARLY ISLAM AS THE ALTERNATIVE TO INCREASING PEOPLE’S ECONOMY: CASE STUDY ON THE MANAGEMENT OF MOSQUE IN YOGYAKARTA - Hasim Hasim (Universitas Sebelas Maret, 2017)
The Indonesian Government has implemented many programs to figure out the problems of poverty and improved the people's economy. However, in reality these programs have not been able to be a solvant step in the issue. Several alternative steps were carried out, one of which was through the finances managed by the mosque which includes zakat, infaq, shadah, hibah (grants) and wakaf. In research conducted by Mualim in Yogyakarta shows that only a few mosques that apply the principle of professionalism in the management of zakat. This study was designed to find a standardized model of mosque financial governance based on the principles and management of the early Islamic baitul maal as an alternative to the improvement of the Ummah/people's economy. The method used is literature study and field research (field research) by using descriptive approach.